PEMBELAJARAN BAHASA INGGRIS UNTUK ANAK TK DAN SD DI GKNS TAMAN UBUD - Hanna Suteja; Atalya Agustin; Meicky Shoreamanis (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2025)
In this era of globalization, English language skills are becoming increasingly important as a means of coping with global dynamics. Early mastery, especially at the kindergarten and elementary school levels, plays a major role in preparing children for the future. However, in reality, English lessons are considered difficult because the teaching methods are not tailored to the characteristics of the students. This program is designed to strengthen children's English skills through a culturally responsive teaching approach that emphasizes cultural relevance in the learning process. In this way, learning does not only focus on linguistic aspects, but also relates the material to the life experiences and cultural identities of the students. The main strategies used in this program are Total Physical Response (TPR) and gamification, which enable children to learn actively, enjoyably, and in accordance with their developmental needs. Adapting the methods to the cultural context helps children feel closer to the material, so that the foreign language does not seem unfamiliar or separate from their daily lives. This English language improvement program is held at the Nafiri Sion Christian Church in Taman Ubud, Tangerang. Although located in a church, this activity is inclusive because it is also attended by children from outside the church community, so that its benefits reach a wider audience.